Heterogeneous Fenton-like CuO-CoOx/SBA-15 catalyst for organic pollutant degradation: synthesis, performance, and mechanism - Li, Jinwei; Wei, Yifei; Liu, Qiang; Guan, Huanhuan; Jiang, Chengchun; Sun, Xiaohui (Frontiers in Chemistry, 2025)
In this study, CuO-CoOx/SBA-15 catalysts were successfully synthesized via ultrasonic impregnation, and their performance in degrading nitrobenzene within a Fenton-like system was investigated. The catalyst materials were characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), inductively coupled plasma mass spectrometry (ICP-MS), scanning electron microscopy (SEM), transmission electron microscope(TEM) and energy-dispersive X-ray spectroscopy (EDS). The CuO-CoOx/SBA-15 catalysts featured well-distributed CuO-CoOx nanoparticles within the mesoporous SBA-15 support. Compared to CuO/SBA-15 and Co3O4/SBA-15 catalysts with similar microstructures, the CuO-CoOx/SBA-15 catalysts exhibited Cu-Co dual active centers and a higher abundance of redox-active sites. During catalytic degradation, H2O2 was continuously activated on the catalyst surface through efficient Cu+/Cu2+ and Co2+/Co3+ redox cycles. The experimental conditions (initial pH, catalyst dosage, and H2O2 dosage) were optimized, resulting in 99% nitrobenzene removal over a wide pH range (3.0–9.0). The primary mechanisms for the oxidation and subsequent removal of nitrobenzene in the CuO-CoOx/SBA-15-H2O2 system were identified as reactions with hydroxyl radicals (·OH).